PEMBERDAYAAN IBU PKK DALAM PEMBUATAN SABUN MINYAK ZAITUN DI KELURAHAN JAGAKARSA - Nopiyanti, Anita; Pusporini, Pusporini; Husniati, Renny; siswantini, Tri (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2024)
PKK is Family Welfare Empowerment. It is a widely recognised term that is usually associated with an association of mothers who have positive activities. PKK is a community organisation to empower women and participate in the welfare development of Indonesia. PKK groups are groups under the village PKK Team that can be formed based on territoriality or activities. The Family Empowerment and Welfare Movement Team (TP PKK) is a partner of the government and community organisations, where the PKK functions as a facilitator, planner, implementer, controller, and activator at each level for the implementation of the PKK program. Family Welfare Empowerment (PKK) as an agent of the community development movement has PKK Principal Programmes. One of the main programmes, the development of cooperative life is a concern. To overcome this, Pengabdi as a team of lecturers and students from the Faculty of Economics and Business UPN Veteran Jakarta, identified opportunities to empower PKK mothers through the development of soap products that are not only environmentally friendly but also provide health and beauty benefits.ABSTRAKPKK adalah Pemberdayaan Kesejahteraan Keluarga. Istilah ini telah dikenal luas yang biasanya diasosiasikan sebagai perkumpulan ibu-ibu yang memiliki kegiatan positif. PKK adalah organisasi kemasyarakatan untuk memberdayakan perempuan dan berpartisipasi dalam pembangunan kesejahteraan Indonesia. Kelompok PKK adalah kelompok-kelompok yang berada di bawah Tim Penggerak PKK desa/kelurahan yang dapat dibentuk berdasarkan kewilayahan atau kegiatan. Tim Penggerak Pemberdayaan dan Kesejahteraan Keluarga (TP PKK) adalah mitra kerja pemerintah dan organisasi kemasyarakatan, dimana fungsi PKK sebagai fasilitator, perencana, pelaksana, pengendali, dan penggerak di masing-masing jenjang untuk terlaksananya program PKK. Pemberdayaan Kesejahteraan Keluarga (PKK) sebagai agen gerakan pembangunan masyarakat mempunyai Program-Program Pokok PKK. Salah satu program pokok, Pengembangan kehidupan berkoperasi menjadi perhatian. Untuk mengatasi hal ini, Pengabdi selaku tim dosen dan mahasiswa dari Fakultas Ekonomi dan Bisnis UPN Veteran Jakarta, mengidentifikasi peluang pemberdayaan ibu-ibu pkk melalui pengembangan produk sabun yang tidak hanya ramah lingkungan tetapi juga memberikan manfaat kesehatan dan kecantikan.